Steering the Nuclear Motion in Singly Ionized Argon Dimers with Mutually Detuned Laser Pulses - Wu, J.; Magrakvelidze, M.; Vredenborg, A.; Schmidt, L. Ph. H.; Jahnke, T.; Czasch, A.; Dörner, R.; Thumm, U. (My University, 2013)
We demonstrate that the vibrational nuclear motion of singly ionized argon dimers can be controlled with two ultrashort laser pulses of different wavelengths. In particular, we observe a striking “gap” in the pump-probe-delay-dependent kinetic-energy release spectrum only if the probe-pulse wavelength exceeds the pump-pulse wavelength. This “frustrated dissociation effect” is reproduced by our two-state quantum mechanical model, validating its interpretation as a pump-pulse-initiated population transfer between dipole-coupled Born-Oppenheimer electronic states of the dissociating Ar+2 molecular ion. Our numerical results also reproduce the measured collapse and fractional revival of the oscillating Ar+2 nuclear wave packet, and, for single-pulse dissociation, the decrease of the kinetic-energy release with increasing laser wavelength.